In Search of a European Identity: An Instrumental Approach - Valeriu Frunzaru; Nicoleta Corbu (Romanian Journal of Communications and Public Relations, 2023)
European identity is often considered a civic identity, as opposed to a cultural one, because of the instrumental approach that people use when making estimations regarding their attitudes toward the EU. We build on Habermas’ view regarding the pragmatic understanding of the impact European decisions have on people’s everyday lives, and argue that the European identity is intrinsically linked to the costs-benefits paradigm of assessing the importance of European decisions. Therefore we consider the European identity must be understood as a civic identity and emphasize the need of a general profile of a citizen who consider himself a European citizen as well, in order to understand the consequences of the European integration. By means of a national survey conducted in May 2011, we show that the European citizen who acknowledges his/her European identity is highly educated, has a high income, lives in urban areas of the country, and is more convinced of the advantages of the Romanian integration in the EU than the disadvantages. In the same time, he/she is more knowledgeable in what concerns basic EU-related information. This confirms the hypothesis of the acknowledgement of the European identity by means of pragmatic identifications of the costs and benefits of the European integration.